Using a small-core graphite calorimeter for dosimetry and scintillator quenching corrections in a therapeutic proton beam. (5th November 2020) - Christensen, Jeppe Brage; Vestergaard, Anne; Andersen, Claus E
Abstract: Organic plastic scintillation detectors (PSDs) are known to produce less light per absorbed dose in highly dense radiations in comparison with e.g. 60 Co gamma beams. This so-called ionization density quenching can be experimentally determined by comparison of the scintillator output with the absorbed dose established with a reference detector. The hypothesis of this work was that a newly developed small-core graphite calorimeter (core size: ø5mm × 7mm) can be used as reference for such measurements. The potential benefit of a calorimetric reference would be to have a robust and accurate reference with well-understood dosimetry properties even in high-intensity FLASH beams. As a first step, the hypothesis was tested by comparing previously established quenching parameter estimates for the BCF-60 scintillating material with data obtained with the new instrument at different depths along the central axis of a 170 MeV scanned proton beam. After the calorimetric measurements, scintillator measurements were acquired under equivalent conditions by positioning the PSD in a replica graphite core nominally identical to the core used for calorimetry. To experimentally document details of the irradiations, the spot width was mapped along the central beam axis using a new technique based on a PSD and a time-to-distance conversion procedure. Analysing the proton data in the framework of the Birks model, the graphite calorimeter gave a k B = ( 11.2 ± 0.4 ) m g M e V − 1 c m − 2 quenching parameter for BCF-60 in agreement with literature values. The consistency between the calorimetric results and the other sources of information supports the validity of the new method, and we therefore aim to apply it for characterization of other detectors in more intense beams where ionometry cannot serve as reference.